Immigrant assimilation and male labor market inequality - Patrick L. Mason (IZA Journal of Migration, 2016)
At the height of the US civil rights movement in the mid-1960s, foreign-born persons were less than 1 % of the African-American population (Kent, Popul Bull, 62:4, 2007). Today, 16 % of America's African diaspora workforce consists of first- or second-generation immigrants and 4 % is Hispanic. Intergenerational improvement is an important source of wage convergence of black immigrants. Unskilled immigrants who arrive in the USA as children and adolescents experience substantial wage assimilation, especially Caribbean-English and African-English immigrants. But both unskilled immigrants arriving as adults and all skilled immigrants fail to catch up to the wage status of either native-born whites or native-born African-Americans. After living in the USA for 9-15 years, first-generation black immigrants will have wage penalties at least as large as native-born African-Americans. The immigration process selects black immigrants who have or who would have achieved middle income or higher status in their country of origin. As such, black immigrants tend to have above average observable characteristics. Nevertheless, black immigrants do not obtain wage assimilation equal to native-born non-Hispanic white male workers.
Keywords: J15; J31; J61; J62; J7; 330; Black immigrants; Assimilation; Discrimination; Immigration; Caribbean; African; Hispanic; Race